Relayout Fasilitas Produksi di UD. X Menggunakan Metode FTC dan Simulasi Diskrit untuk Efisiensi Material Handling - Adipura, Rahma; Wati, Putu Eka Dewi Karunia (Fakultas Teknik UMRI, 2025)
Inefficient material handling can lead to increased production time, higher operational costs, and a greater risk of product damage. UD. X is a manufacturing company that produces motorcycle spare parts and is currently experiencing inefficiencies in its facility layout, resulting in suboptimal material flow. This study aims to redesign the facility layout to improve the efficiency of the material handling system. The methods used include the From-To Chart (FTC) for analyzing material movement between workstations, as well as discrete event simulation to evaluate the performance of layout alternatives. Data collected includes inter-departmental distances, frequency of material movement, process time, and total material travel distance. The results show that the proposed layouts successfully reduce material travel distance and handling costs. The best alternative achieved a total travel distance of 1080.05 meters and a material handling cost of Rp27,954.